Wie steht es um die Innovationsfähigkeit Deutschlands? - Hanna Hottenrott; Bettina Peters; Christian Rammer (Wirtschaftsdienst, 2024)
– Innovation is crucial to economic development. Innovation expenditures in Germany's business sector as well as public funding for science and research have been increasing in the past decade. However, the share of businesses with innovations - especially among the small- and medium-sized ones - decreased from 70% in the 2010s to 50% in 2022. Likewise the share of sales from new products and collaborations between science and industry have been declining in recent years. This might be explained by certain barriers to innovation. Increasingly important hampering factors are the lack of qualified employees and the burden of regulation and bureaucracy. Policy measures to support Germany's innovation capacity should tackle the reduction of such constraints that currently reduce the return to investment into R&D and innovation.
Keywords: I28; O31; O38; 330; Innovation; Deutschland; Innovation; Deutschland